Psychological Stress as A Predictor of Testosterone Suppression and Spermatogenic Failure in Idiopathic Non-Obstructive Azoospermia: Administrative and Clinical Perspectives - ABID, NABEELA; ALI, MASHOOQUE; RAZZAQ, FOUZIA ABDUL; KHALID, ASIMA; BASHIR, FAIZAN (Pakistan Journal of Medical & Health Sciences, 2026)
Background: Idiopathic non-obstructive azoospermia (iNOA) represents a type of grave male infertility, which is accompanied by the inability to produce spermatogenesis with no apparent cause. There is emerging evidence that psychological stress could interfere with hypothalamic-pituitary-gonadal axis through neuroendocrine pathways and be a cause of reproductive dysfunction. There is however scarcity of information on stress and hormonal imbalance interaction and infertility risk in the developing world like Pakistan. Objective: To evaluate the association between psychological stress, hormonal parameters, and clinical characteristics in men with iNOA compared with fertile controls. Methods: This was a case-control study done between January 2025 to December 2025 in three tertiary care hospitals in Punjab, Pakistan. They recruited 48 participants (30 iNOA patients with a diagnosis and 18 fertile controls). The demographic, lifestyle, and clinical data were gathered. Hormone tests were follicle-stimulating hormone (FSH), luteinizing hormone (LH), testosterone, prolactin, and estradiol. The measures of psychological stress were the Perceived Stress Scale (PSS) and the tests of anxiety and depression. Statistical software SPSS version 25 was used to do statistical analysis. The group difference was compared by using independent t-tests and the relationship and predictors by using Pearson correlation and multiple regression. A p-value of less than 0.05 was taken to be significant. Findings: iNOA patients had considerably more perceived stress, anxiety and depression (p < 0.01). They were also found to have a low testicular volume and lower Johnsen scores, which was evidence of poor spermatogenesis. The level of testosterone was much lower and gonadotropins demonstrated an upward trend. Stress was found to have a negative relationship with testosterone and positive relationship with gonadotropins. The regression analysis has found perceived stress to be an independent variable predicting the level of testosterone. Conclusion: Hormonal dysregulation in men with iNOA is strongly linked to psychological stress, which facilitates a biopsychosocial explanation of male infertility. By incorporating psychological testing and lifestyle modification into infertility treatment, it is possible to enhance reproductive outcome.